Production of high-octane gasoline from straight-run gasoline on ZSM-5 modified zeolites; Theoretical Foundations of Chemical Engineering; Vol. 48, iss. 1 - Erofeev V. I. Vladimir Ivanovich (2014, 2014)
Title screen